1988
DOI: 10.1016/0304-3959(88)90122-4
|View full text |Cite
|
Sign up to set email alerts
|

Naloxone does not alter the perception of pain induced by electrical and thermal stimulation of the skin in healthy humans

Abstract: It has been hypothesized that, in the absence of acute or chronic pain, a tonically active system exists involving opioid peptides, which ensures a certain level of pain insensitivity. Although various studies have failed to support this concept, it has been reported that in conditions of both experimentally induced and clinical pain, high doses of the opioid antagonist naloxone induced a state of hyperalgesia and thus seemed to set off this hypothetical system. Lower doses were, however, without effect or eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 14 publications
2
26
0
Order By: Relevance
“…The effects of 碌-opioid receptor blockade on experimental pain are inconsistent, with reports of pain increasing after naloxone administration (Buchsbaum et al, 1983;Borras et al, 2004), not changing (El-Sobky et al, 1976;Grevert and Goldstein, 1978), or decreasing (Stacher et al, 1988;Al'Absi et al, 2004). This inconsistency may be due to individual differences in pain sensitivity (Buchsbaum et al, 1983) or could be dose-related.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of 碌-opioid receptor blockade on experimental pain are inconsistent, with reports of pain increasing after naloxone administration (Buchsbaum et al, 1983;Borras et al, 2004), not changing (El-Sobky et al, 1976;Grevert and Goldstein, 1978), or decreasing (Stacher et al, 1988;Al'Absi et al, 2004). This inconsistency may be due to individual differences in pain sensitivity (Buchsbaum et al, 1983) or could be dose-related.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies report that naloxone increased pain after noxious stimuli (Buchsbaum et al 1983), whereas others suggest that there is no alteration in pain threshold but an increase in pain-associated anxiety (Grevert andGoldstein 1977, 1978;Stacher et al 1988). Naloxone administration also has effects on clinical pain: it both enhances baseline clinical pain and diminishes the analgesic effectiveness of a placebo (Grevert et al 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Early studies by Buchsbaum and colleagues demonstrated naloxone-related hyperalgesia (Buchsbaum et al 1977;Davis et al 1978;Buchsbaum et al 1983), although these effects were limited to specific individuals (e.g., "pain insensitive" participants) or conditions (e.g., prolonged or intense stimulation). Other studies have reported that naloxone has no effect on forearm ischemic pain (Grevert and Goldstein 1977;Grevert et al 1983a;Grevert et al 1983b;Posner and Burke 1985), cold pressor pain (Grevert and Goldstein 1978;McCubbin and Bruehl 1994), or electrocutaneous pain in response to stimulation applied to the finger (Bromm et al 1983), forearm (El-Sobky et al 1976), ear (Stacher et al 1988), or teeth (Ernst et al 1986). Finally, a few studies have suggested that, in some cases, opioid antagonists may actually inhibit pain (Volavka et al 1979;Tassorelli et al 1995;Janssen and Arntz 1997).…”
Section: Introductionmentioning
confidence: 99%